2018
DOI: 10.1177/1359105318755263
|View full text |Cite
|
Sign up to set email alerts
|

Health anxiety and associated constructs in children and adolescents with congenital heart disease: A CHAMPS cohort study

Abstract: This study explored health anxiety and associated constructs in children and adolescents with congenital heart disease and typically developing children and adolescents. A total of 84 participants (7-16 years) completed measures of health anxiety, intolerance of uncertainty, anxiety sensitivity, and DSM-IV anxiety disorder symptom categories. Results demonstrated that children and adolescents with congenital heart disease experienced significantly higher levels of health anxiety and associated constructs compa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(46 citation statements)
references
References 46 publications
2
33
0
6
Order By: Relevance
“…In this paper, we seek to extrapolate evidence from the HA literature to inform how health-related worries in children and young people may be managed in practice, and more specifically, how this might relate to infectious disease pandemics such as Health anxiety in children and young people HA as a disorder typically presents in early or middle adulthood (APA, 2013;Rask et al, 2016). There is some evidence to suggest that HA does occur in childhood and adolescence (Eminson et al, 1996;Oliver et al, 2018;Rask et al, 2012;Rask et al, 2016;Sirri et al, 2015;van Geelen et al, 2015;Wright and Asmundson, 2003), yet studies examining the prevalence of HA in children and young people suggest that few meet the full diagnostic criteria (Rask et al, 2016). This may be partly due to a lack of tailored, developmentally appropriate descriptions of how HA presents in children and young people (Fritz et al, 1997;Rask et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we seek to extrapolate evidence from the HA literature to inform how health-related worries in children and young people may be managed in practice, and more specifically, how this might relate to infectious disease pandemics such as Health anxiety in children and young people HA as a disorder typically presents in early or middle adulthood (APA, 2013;Rask et al, 2016). There is some evidence to suggest that HA does occur in childhood and adolescence (Eminson et al, 1996;Oliver et al, 2018;Rask et al, 2012;Rask et al, 2016;Sirri et al, 2015;van Geelen et al, 2015;Wright and Asmundson, 2003), yet studies examining the prevalence of HA in children and young people suggest that few meet the full diagnostic criteria (Rask et al, 2016). This may be partly due to a lack of tailored, developmentally appropriate descriptions of how HA presents in children and young people (Fritz et al, 1997;Rask et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Together with the current findings and retrospective reports suggesting that adult HA is often preceded by similar symptoms in childhood and adolescence (Noyes et al, 2002), the overall evidence suggests continuity of HA across the life span. As outlined in the introduction, important findings from cross-sectional studies on children and adolescents have shown that HA is associated with a broad array of other types of psychopathology (Oliver et al, 2018;Rask et al, 2016;Rimvall et al, 2019;Sirri et al, 2015;Wright et al, 2016). Crucially, even in the adjusted analyses, there was still evidence of an independent effect of high HA at age 11 on the risk of high HA at age 16, since the findings were only partially explained by chronic somatic illness.…”
Section: Discussionmentioning
confidence: 95%
“…As outlined in the introduction, important findings from cross‐sectional studies on children and adolescents have shown that HA is associated with a broad array of other types of psychopathology (Oliver et al, 2018; Rask et al, 2016; Rimvall et al, 2019; Sirri et al, 2015; Wright et al, 2016). Crucially, even in the adjusted analyses, there was still evidence of an independent effect of high HA at age 11 on the risk of high HA at age 16, since the findings were only partially explained by chronic somatic illness.…”
Section: Discussionmentioning
confidence: 99%
“…8,12,33,39 Young children also present to cardiac neurodevelopmental programs with dysregulated sleep patterns and with separation or medical anxiety. 24,33,39,45,48,76,77 Once children reach preschool, grade retention is often considered by parents, sometimes at the recommendation of schools or providers. Grade retention recommendations are most common among children with histories of repeat or prolonged hospitalisations, and who have reduced stamina and endurance.…”
Section: Referral Patternsmentioning
confidence: 99%
“…In preschool and early elementary years, other challenges become more prominent, including learning delays or disability, 30,33,[36][37][38][39] fine and graphomotor output challenges, 1,8,[40][41][42] poor attention, 29,36,39,43 and impaired social functioning. 1,33,34,39,44 Young children with congenital heart disease are at high risk for behaviour and mood problems, 16,45,46 and may appear less socially and emotionally mature than typically developing peers. 25,[47][48][49][50] Birth through five assessment battery goals…”
Section: Introductionmentioning
confidence: 99%